2009
DOI: 10.1080/00016480802468153
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of neural stem cells overexpressing glia-derived neurotrophic factor promotes facial nerve regeneration

Abstract: NSCs exhibited sustained and robust GDNF expression in culture and following implantation. Nerve action potential amplitude, axonal area, and axonal number were significantly greater in the NSCs-GDNF group than in the NSCs or empty NC groups. Axonal area and number were also greater in the NSCs-GDNF group than the SCs-GDNF group, although this was not statistically significant. The enhanced regeneration observed in the NSCs-GDNF group was accompanied by increased labeling for S100, NF, and βIII tubulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
0
37
1
6
Order By: Relevance
“…Pre-clinical experiments have demonstrated that stem cells show promising results in differentiation into neuronal-like cells [226,228,232,233,240] and their secretion of growth factors [229,241,242]. Shi and colleagues [243] stated the potential of glia-derived neurotrophic factor expressing neural stem cells in the regeneration of facial nerve gap in rats.…”
Section: Cellular Systemsmentioning
confidence: 99%
“…Pre-clinical experiments have demonstrated that stem cells show promising results in differentiation into neuronal-like cells [226,228,232,233,240] and their secretion of growth factors [229,241,242]. Shi and colleagues [243] stated the potential of glia-derived neurotrophic factor expressing neural stem cells in the regeneration of facial nerve gap in rats.…”
Section: Cellular Systemsmentioning
confidence: 99%
“…Early intervention is preferable if denervated muscles have no opportunity to be reinnervated from regenerating peripheral axons or when reinnervation is delayed, as often occurs in brachial plexus injuries. [7][8][9][10][11][12]33 Some traditional methods, such as stimulation 5 and rehabilitation 6 are not effective in arresting denervated muscle atrophy. Prevention of muscle atrophy using fetal NSCs following denervation may be of therapeutic benefit in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…12,34,35 Recent progress in the biology of NSCs has made it possible to routinely expand neural progenitor cells obtained from a small amount of fetal CNS tissue in vitro as floating cell aggregates called neurospheres. 33,34 Therefore, this may overcome the practical problems associated with fetal tissue transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…8 weeks after the implantation, comparable morphological rescues in mid-graft, including the number of axons and area of nerve fibers, were observed in the seeded implants and were comparable to autografts. Shi et al further investigated the combined effect of cell replacement therapy with sustained neurotrophic factor delivery [121]. NSCs and SCs were modified to express GDNF and infused into PLGA tubes followed by implantation into rats with facial nerve transections in two separate sets of experiments.…”
Section: Cell-carriers With Biodegradable Materialsmentioning
confidence: 99%